Infant gut microbiota restoration: state of the art - Katri Korpela; Willem M. de Vos (Gut Microbes)
The gut microbiota has a central role in the programming of the host’s metabolism and immune function, with both immediate and long-term health consequences. Recent years have witnessed an accumulation of understanding of the process of the colonization and development of the gut microbiota in infants. The natural gut microbiota colonization during birth is frequently disrupted due to C-section birth or intrapartum or postpartum antibiotic exposure, and consequently aberrant gut microbiota development is common. On a positive note, research has shown that restoration of normal gut microbiota development is feasible. We discuss here the current understanding of the infant microbiota, provide an overview of the sources of disturbances, and critically evaluate the evidence on early life gut microbiota restoration for improved health outcomes by analyzing published data from infant gut microbiota restoration studies.